Modelagem matemática do processo de evaporação do licor negro proveniente do sistema de lavagem da polpa celulósica - Diel, Cristiano Luiz (2013)
The pulp and paper industries are major consumers of energy. The plant of black liquor evaporation consumes significant portion of this energy. Any effort to improve their energy efficiency is beneficial to the industry. The computer simulation is a powerful tool to aid the understanding of industrial processes and may help identify mechanisms involved in the prediction of responses to changes in operating conditions and optimization of process control. The objective of this work is the development of a mathematical model phenomenological representing the evaporation plant of Klabin Papéis Monte Alegre (KPMA) and the use of it to study and improve operational conditions of the plant. To achieve this goal, firstly it was developed a simplified model based on the work of other authors. The model was built in Maple ® platform. The model was built from mass and energy balances and phase equilibrium equations. Correlations were used to estimate properties, e. g. boiling point raise, enthalpies of the liquor, steam and condensate. The model reproduced well the results of the authors, with the largest percentual error equal to 5.5% and most of the parameters with percentual errors less than 1%. The model was adapted to represent the first effect of evaporation plant of KPMA. Historical operating data were used to compare the model results. Good results were found for temperature and solid content of the liquor. Good results were found for mass flows in some effects, but the model could not effectively predict the mass flow of all effects and the variables related to the flash tanks. The differences are attributed mainly to considerations of steady state and saturated vapor with no entrainment of particles in the liquor and the use of literature correlations to predict the properties of the liquor that do not correspond to the liquor used.